`PENINGKATAN KETERAMPILAN BERBICARA MELALUI METODE DEBAT PLUS PADA MATA KULIAH BERBICARA - Lalita Melasarianti (Jurnal Lingua Idea, 2018)
Each prospective teacher learning at Indonesian Language Education Study Program, Language Education Department, Jenderal Soedirman University should sophisticatedly master and acquire public speaking skills and expertise in various situations. A prospective teacher should also have a strong character equipped with the spirit of an educator. By having public speaking practices, it is expected that the prospective teachers (students) may achieve the intended goals. Speaking practices mean sharpening our mind and language. When someone is able to speak in front of public very well, then s/he may be considered to have a good personality. Debate Plus is a method used by the lecturers of Indonesian Language Education Study Program in speaking classes to achieve the effective learning objectives.